2022
DOI: 10.14444/8223
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Women on Editorial Boards of Medline-Indexed Spine, Neurosurgery, and Orthopedic Journals

Abstract: Background: Both neurosurgery and orthopedic surgery are male-dominated specialties. However, the prevalence of women appears to be even lower in the spine surgery field. We intend to determine this prevalence on the editorial boards of spine, neurosurgery, and orthopedic journals.Methods: The gender of editorial board members of Medline-indexed spine, neurosurgery, and orthopedic journals was systematically analyzed in 2019, and female representation was compared among these fields.Results: In the 34 journals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This pattern indicates that even when females were granted research authorship, their involvement seldom extended to leadership roles. This gap also translates into poorer representation of women as editorial board members, contributing to 8.58% of all board members in neurosurgery journals and 5.53% in spinal journals [ 22 , 27 ]. This may be one of the reasons for decreased representation of women as article authors, in addition to the attrition of women in the advancement of neurosurgical careers.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern indicates that even when females were granted research authorship, their involvement seldom extended to leadership roles. This gap also translates into poorer representation of women as editorial board members, contributing to 8.58% of all board members in neurosurgery journals and 5.53% in spinal journals [ 22 , 27 ]. This may be one of the reasons for decreased representation of women as article authors, in addition to the attrition of women in the advancement of neurosurgical careers.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies had reported inadequate representation of women in editorial boards across various medical fields. This issue appears to be particularly pronounced in surgical specialties such as orthopedics, anesthesia, general surgery, spine surgery, neurosurgery, when compared to internal medicine disciplines 4,5,8–11 . Choi and Miller had noted proportional representation of female otolaryngologists in journal editorships and editorial memberships 7 .…”
Section: Discussionmentioning
confidence: 99%
“…This issue appears to be particularly pronounced in surgical specialties such as orthopedics, anesthesia, general surgery, spine surgery, neurosurgery, when compared to internal medicine disciplines. 4 , 5 , 8 , 9 , 10 , 11 Choi and Miller had noted proportional representation of female otolaryngologists in journal editorships and editorial memberships. 7 However, after examining data from 9 otolaryngology journals, Litvack et al pointed that, despite observing an increase in the representation of women in editorial boards from 7.2% to 17.7% between 1997 and 2017 ( p = .0001), and an increase in the proportion of women associate/section editors from 9.3% to 20.9% ( p = .09), women were still inadequately represented in editorial boards.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite this fact the representation of women in the editorial board of neurosurgery journals was very low. 15 …”
Section: Academics Leadership and Administrationmentioning
confidence: 99%